Lempel, Even, and Cederbaum Planarity Method - Noma, Alexandre; Fernandes, Cristina G. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2004: Anais do XVII Concurso de Teses e Dissertações, 2004)
We present a simple pedagogical graph theoretical description of Lempel, Even, and Cederbaum (LEC) planarity method based on concepts due to Thomas. A linear-time implementation of LEC method using the PC-tree data structure of Shih and Hsu is provided and described in details. We report on an experimental study involving this implementation and other available linear-time implementations of planarity algorithms.